2021
DOI: 10.21203/rs.3.rs-44833/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene co-expression analysis of tomato seed maturation reveals tissue-specific regulatory networks and hubs associated with the acquisition of desiccation tolerance and seed vigour

Abstract: Background During maturation seeds acquire several physiological traits to enable them to survive drying and disseminate the species. Few studies have addressed the regulatory networks controlling acquisition of these traits at the tissue level particularly in endospermic seeds such as tomato, which matures in a fully hydrated environment and does not undergo maturation drying. Using temporal RNA-seq analyses of the different seed tissues during maturation, gene network and trait-based correlations were used t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As inference from gene co‐expression analyses suggested that MtABI4 was linked to longevity (Bizouerne et al., 2021; Verdier et al., 2013), the longevity of the Mtabi4 seeds was determined by monitoring the loss of germination of after‐ripened seeds during storage at 35°C and 75% RH. Seed lifespan was reduced by 75% in Mtabi4 compared with the WT (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As inference from gene co‐expression analyses suggested that MtABI4 was linked to longevity (Bizouerne et al., 2021; Verdier et al., 2013), the longevity of the Mtabi4 seeds was determined by monitoring the loss of germination of after‐ripened seeds during storage at 35°C and 75% RH. Seed lifespan was reduced by 75% in Mtabi4 compared with the WT (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Gene co‐expression analyses during maturation in seeds of Medicago truncatula and Solanum lycopersicum (tomato) identified ABI4 as a transcription factor correlated with seed longevity (Bizouerne et al., 2021; Verdier et al., 2013). ABI4 is a versatile enhancer of ABA signal transduction during development and in response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular processes involved in DT acquisition and reinduction have been well studied at the transcriptomic level, which resulted in identification of DT-associated gene networks. These DT-associated genes were mainly associated with cell protection functions (e.g., antioxidants and protective compounds), promoting cell survival upon severe dehydration (Delahaie et al, 2013;Terrasson et al, 2013;Verdier et al, 2013;Costa et al, 2015;Righetti et al, 2015;Gonzaĺez-Morales et al, 2016;Costa et al, 2017;Bizouerne et al, 2021). These DTassociated gene networks are transcriptionally regulated at potentially two levels: a more explored direct transcriptional regulation via the action of transcriptional activators/repressors such as transcription factors and/or at the epigenetic level via the regulation of the chromatin accessibility rendering the DTassociated genes in a repressed or activable states.…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, topological features of a system and network architectural analyses can be employed to identify novel molecular players and regulators in various regulatory networks in diverse systems [14,[26][27][28][29]. Among these network features, modules (clusters of highly correlated genes) and hubs (high degree; the number of edges of a node) have been used to predict major regulators in Arabidopsis and tomato [14,30]. Modeling dynamic transcriptional processes in TRNs is challenging, but it can hold a great promise to comprehend how plants respond to water scarcity.…”
Section: Introductionmentioning
confidence: 99%